Microstructural, morphological, and optical properties of Fe2O3 nanoparticles obtained from Fe-MIM MOF - Olalekan C Olatunde; Murendeni P Ravele; Tunde L Yusuf; Damian C Onwudiwe (Nano Express)
This study explores the microstructural, morphological, and optical properties of Fe _2 O _3 nanoparticles synthesized from the pyrolysis of ZIF-8 like Fe-2-methyl imidazole (MIM) metal–organic frameworks (MOFs). Using X-ray diffraction (XRD) profile analysis methods, including the modified Scherrer, Williamson–Hall (W-H), size strain plot, and Halder-Wagner methods, the impact of annealing temperature on the microstructural parameters and crystal defects of the obtained Fe _2 O _3 nanoparticles was investigated. The nanoparticles exhibited high crystallinity and a rhombohedral α -Fe _2 O _3 phase. Morphological analysis through transmission electron microscopy (TEM) revealed distinct structural features, while UV–vis spectroscopy was employed to examine their optical properties. The results indicated that higher annealing temperatures enhance crystallinity, reduce defect density, and improve atomic mobility. This comprehensive analysis provides valuable insights into the synthesis-structure–property relationships of Fe _2 O _3 nanoparticles, highlighting their potential applications in applications such as gas sensing and photocatalysis.